Paraguay : Stand-By Arrangement-Request for Extension. (IMF Staff Country Reports; Country Report, 2006)
The staff report for the Stand-By Arrangement on Paraguay highlights the request for a two-month extension by the authorities. The authorities are not requesting any change in the cumulative access under the arrangement and intend to continue to treat it as precautionary. The policy of publication of staff reports and other documents allows for the deletion of market-sensitive information. The continuous performance criteria on the nonaccumulation of arrears and noncontracting of short-term external debt appear to have been met.